Integrating Digital Literacy Into EFL Classroom: A Study of Theory of Planned Behavior - Alfia, Nurul; sumardi, Sumardi; Kristina, Diah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Beliefs take a vital role in influencing students' decision about integrating digital literacy in EFL classroom. This case study investigated students' behavioral, control, and normative beliefs toward integrating digital literacy into the EFL classroom. This research used the Theory of Planned Behavior initiated by Ajzen to collect and analyze the data. The results of interviews and observations highlighted students' integration of digital literacy into EFL classroom referred to several beliefs. The behavioral beliefs (attitude toward advantages of a behavior) about the value of digital literacy for its effectiveness and efficiency potential to find information, to promote students cognitive skills and ethical awareness, and to improve English proficiency; normative beliefs (about social support) about the meeting of the expectation of school, teachers, parents, and friends; and control beliefs (about perceive behavioral control) about the opportunity and the availability to interact with the technology. This study highlighted a substantive theory related to the findings: Students' positive beliefs about integrating digital literacy into EFL classroom influence students' learning strategy. By having positive beliefs about the outcomes that students will get (behavioral beliefs), support from family, teachers, and the school environment (normative beliefs), as well as beliefs about the presence of factors that may facilitate or hinder the performance (control beliefs), students demonstrate the tendency to always use digital technology in learning English.